Pulmonary Cryptococcosis due to Cryptococcus laurentii Co-infection with Miliary Tuberculosis in Adolescent Patient in Indonesia: Case Report - Widyasari, Domas Fitria; Daniwijaya, M Edwin Widyanto; Siswanto, Siswanto; Wirastuti, Fita; Wibawa, Tri (Rumah Sakit Akademik Universitas Gadjah Mada, 2025)
AbstractBackground: Non-neoformans cryptococci were previously considered to be saprophytes and nonpathogenic to humans. Cryptococcus laurentii is commonly found in the environment and pigeon feces and has been reported to be an emerging human fungal pathogen that causes infection in the immunocompromised host. Here, we report a unique case of pulmonary cryptococcosis coinfection with Miliary Tuberculosis.Case: A 14-years old adolescent underweight boy was admitted to the Emergency Unit with the chief complaint of fever, cough, chest pain, breathlessness, night sweats, malaise, and weight loss. He was referred from Public Health Center in Sleman Yogyakarta with Miliary Tuberculosis and consumed six weeks of fixed-dose combinations of the first-line anti-tuberculosis drug. Microbiology culture of good quality patient sputum revealed Cryptococcus laurentii along with Klebsiella oxytoca. The patient was diagnosed with Pulmonary Cryptococcosis. The patient's symptoms, especially fever and chest pain, were not improved by oral Fluconazole 200 mg treatment. However, he had an excellent response to Levofloxacin 500 mg during hospitalization and oral Fluconazole therapy at 400 mg/day for eight weeks. After eight weeks of Fluconazole treatment, the patient got well, and then Fluconazole was stopped. Anti-tuberculosis was treated for six months, and no recurrence was found.Conclusion: This article reports the rare pulmonary involvement of Cryptococcus laurentii in adolescent patients with Miliary Tuberculosis patient in Indonesia. A high degree of pulmonary mycosis suspicion and techniques improvement for respiratory specimen collection, culture, and identification contribute to early diagnosis and fungal infection treatment. In addition, interprofessional discussion can improve patient treatment and outcomes.